2022
DOI: 10.1039/d1cc06863f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the aromatic backbone twist in dipyrrolonaphthyridinediones

Abstract: This communication describes the photophysical behavior of three analogs of cyclophane bearing the dipyrrolonaphthyridinedione (DPND) core. In these molecules, intersystem crossing (ISC) can be successfully induced by distinct changes in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…From the above, it can be seen that the bending of the aromatic core by tethering leads to red-shifted absorption and PL spectra, smaller band gaps, larger Stokes shifts, and lower PL quantum yields. This is consistent with the observation in some previous studies. , …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…From the above, it can be seen that the bending of the aromatic core by tethering leads to red-shifted absorption and PL spectra, smaller band gaps, larger Stokes shifts, and lower PL quantum yields. This is consistent with the observation in some previous studies. , …”
Section: Resultssupporting
confidence: 94%
“…This is consistent with the observation in some previous studies. 36,48 Next, we studied the chiroptical properties of the tethered aromatic lactams. P and M enantiomers of 2L-Me-C 10 , 4L-Me-C 12 , 4L-Bu-C 12 , and 6L-Bu-C 14 were successfully separated by using chiral HPLC.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations for some arylated DPNDs revealed that the expected deviation from the core plane mainly caused by the presence of arene rings at position 3 and 9 should be no greater that 8°. 30 a In order to test how high distortion influences of the photophysical aspects, we assembled three analogues of cyclophanes based on the DPND core (1o–r) 20 that differ in a length of an alkane bridge. X-ray analysis of 1p revealed that the distortion from the planarity reaches 28° ( Fig.…”
Section: The Optoelectronic Properties Of Dipyrrolonaphthyridinedione...mentioning
confidence: 99%
“…Another tested strategy towards 1a involved dipyrroyl derivative 4 as a source of pyrrole rings. Compound 4 can be easily synthesized from either 2,5-dimethoxytetrahydrofurane and succinamide 18,20 or pyrrole and 3. 21 Indeed, subjecting 4 to the typical Vilsmeier-Haack reaction conditions (DMF/POCl 3 ) resulted in the formation of 1a, but still with low efficiency (Scheme 2).…”
Section: Synthesis Of Dipyrrolonaphthiridinedionesmentioning
confidence: 99%